THE ROLE OF TEACHERS IN INSTILLING THE VALUES OF TOLERANCE IN MADRASAH IBTIDAIYAH STUDENTS - Abdul Chalim; Slamet Pamuji; Moh. Miftahul Arifin; Ahmad Ridwan; Muhammad Rusdi (Adisam Publisher, 2024)
The role of teachers in education is very important to shape the character of students at school. The teacher's role as an educator is an example, role model, and figure identified by students. In schools, religious culture and religious tolerance will be formed if teachers prepare themselves with qualities such as responsibility, authority, independence and discipline. The aim of this research is to find out how teachers play a role in instilling the values of tolerance in Madrasah Ibtidaiyah students. Research findings show that teachers play an important role in instilling attitudes of tolerance in their students. The strategies they use for teaching include collaboration in class, using learning materials that support the principles of tolerance, and holding open discussions. These findings show how teachers try to build students' characters who are open and tolerant of differences. This strengthens the contribution of education to building a more just and inclusive society. This research can contribute to curriculum development and teacher training to improve the results of efforts to instill the value of tolerance at the madrasah ibtidaiyah level. Instilling the value of tolerance is carried out through learning activities using methods such as providing examples, providing direction, habituation, storytelling activities, game activities, and the use of media. The aim of implementing tolerance for students at school is as a means of training so that students are more able to implement and develop a broader attitude of tolerance when living in society.